The Molecular Epidemiology of Clade 2.3.4.4B H5N1 High Pathogenicity Avian Influenza in Southern Africa, 2021–2022 - Celia Abolnik; Thandeka Phiri; Belinda Peyrot; Renee de Beer; Albert Snyman; David Roberts; Katrin Ludynia; Frances Jordaan; Michele Maartens; Zehaad Ismail; Christine Strydom; Gerbrand van der Zel; et al. (Viruses, 2023)
In southern Africa, clade 2.3.4.4B H5N1 high pathogenicity avian influenza (HPAI) was first detected in South African (SA) poultry in April 2021, followed by outbreaks in poultry or wild birds in Lesotho and Botswana. In this study, the complete or partial genomes of 117 viruses from the SA outbreaks in 2021–2022 were analyzed to decipher the sub-regional spread of the disease. Our analysis showed that seven H5N1 sub-genotypes were associated with the initial outbreaks, but by late 2022 only two sub-genotypes still circulated. Furthermore, SA poultry was not the source of Lesotho’s outbreaks, and the latter was most likely an introduction from wild birds. Similarly, SA and Botswana’s outbreaks in 2021 were unrelated, but viruses of Botswana’s unique sub-genotype were introduced into SA later in 2022 causing an outbreak in ostriches. At least 83% of SA’s commercial poultry cases in 2021–2022 were point introductions from wild birds. Like H5N8 HPAI in 2017–2018, a coastal seabird-restricted sub-lineage of H5N1 viruses emerged in the Western Cape province in 2021 and spread to Namibia, causing mortalities in Cape Cormorants. In SA ~24,000 of this endangered species died, and the loss of >300 endangered African penguins further threatens biodiversity.